(untitled) (Research, Society and Development, 2021)
This study sought to understand the operational process of purchases of family farming products and their economic organizations for school feeding in five medium and large municipalities in Minas Gerais, Brazil, namely: Belo Horizonte, Governador Valadares, Juiz de Fora, Montes Claros and Uberlândia. The objective of the study is to analyze the process of implementation of the National School Feeding Program (PNAE) in the aforementioned municipalities and the institutional devices (rules and regulations) created to operationalize the commercialization and purchase of products from associations and cooperatives of family farming that they particularize and condition the implementation of public policy. To this end, a qualitative methodological approach was used, with a descriptive character. Still, despite the PNAE being a public policy governed by national legislation, Law No. 11,947 of 2009, social interactions and the construction of institutional devices created in local contexts particularize the implementation of this public policy. It was found that a large part of city halls, as well as family farming associations and cooperatives, tend to create institutional devices, be they normative and coercive, collective agreements or even self-regulatory devices that modify the institutional design of the operationalization of the PNAE and create characteristics even more specific, if compared to the municipalities that only follow the determinations set out in the federal legislation.